Fratelli Tutti - An Interreligious Perspective - Fredericks, James L. (Studies in interreligious dialogue, 2022)
The encyclical Fratelli Tutti carries great import for the work of interreligious dialogue and the Catholic Church’s relationship with other religious communities. The author makes three claims: (1) FT is the most extensive papal statement on dialogue since Ecclesiam Suam (1964); (2) unlike previous papal statements on interreligious dialogue, FT does not place the Church’s ministry of dialogue within a theology of religions in which humankind’s universal religious aspirations are fulfilled in Jesus Christ; (3) FT is a social encyclical and Pope Francis construes interreligious dialogue in terms of the Catholic Church’s social ethics. Our dialogues must be aimed at the development of new forms of social solidarity among religious communities.